Predictors of youth unemployment duration and impact evaluation of job creation program in East Gojjam Zone - Nigusie Gashaye Shita; Metadel Azeze Mekonnen; Yeshiwas Ewinetu Tegegne; Misganaw Mekonnen Nigussie; Awoke Fetahi Woudneh (PLoS ONE, 2025)
Youth unemployment in the East Gojjam Zone is a critical issue. This study focuses on identifying the factors that influence unemployment duration and evaluating the impact of job creation programs on the well-being of youth in this region. We employed Cox regression to analyze the determinants of unemployment duration and used propensity score matching to assess the welfare effects of job creation initiatives. Our multistage cluster sampling revealed a youth unemployment rate of 33.3% (95% CI: 27.3–39.3). Over half of the unemployed youth transitioned to employment within four years, with 25% securing jobs within two years. Participation in job creation programs led to an average earnings increase of 1,069.716 birr, though retention in these programs was low at 49%. The findings reveal a connection between prolonged unemployment, skill mismatches, financial constraints, limited work experience, weak social networks, low income, and a preference for public-sector employment. To effectively address these challenges, interventions must focus on improving job accessibility, aligning vocational training with labor market needs, promoting financial inclusion, and enhancing social support systems.